Comparative effectiveness of pharmacist care delivery models for hepatitis C clinics. (15th March 2019) - Naidjate, Safiya S; Zullo, Andrew R; Dapaah-Afriyie, Ruth; Hersey, Michelle L; Marshall, Brandon D L; Winkler, Richelle Manalang; Berard-Collins, Christine
Abstract: Purpose: The optimal health care delivery models for providing services to patients with infections caused by hepatitis C virus (HCV) remain unknown. Pharmacist involvement may be a key component of optimal HCV care delivery. We examined the comparative effectiveness of a pharmacist-managed HCV clinic versus a pharmacist-assisted HCV clinic. Methods: This retrospective cohort study used electronic health record data on patients ≥18 years old initiating HCV treatment at a pharmacist-managed clinic or a pharmacist-assisted clinic within a single health-system between January 2015 and June 2017. Outcomes included treatment completion, sustained virologic response 12 weeks following treatment completion (SVR-12), and dispensation of direct-acting antiviral agents at the institution-based specialty pharmacy. Inverse probability of treatment-weighted (IPTW) logistic regression models were used to compare outcomes between the 2 clinic models. Results: A total of 127 patients initiated HCV treatment therapy: 64 patients from the pharmacist-managed clinic and 63 patients from the pharmacist-assisted clinic. The cohort had a mean age of 55 years, was 51% male, and 68% white. In IPTW analyses, there was no difference in treatment completion (odds ratio [OR], 1.1; 95% confidence interval [CI], 0.1–13.8; p = 0.93), achievement of sustained virologic response at 12 months (SVR-12) (OR, 1.0; 95% CI, 0.2–4.5; p = 0.62), or use of institution-based specialty pharmacy (OR, 0.6; 95% CI, 0.2–1.7; p = 0.33) between pharmacist-managed and pharmacist-assisted clinics. Conclusion: There were no significant differences in outcomes between patients receiving care at the pharmacist-managed HCV clinic and the pharmacist-assisted clinic. Given the frequency of SVR-12 achieved in both groups, both pharmacist-managed and pharmacist-assisted clinic models may be reasonable alternatives for providing outpatient HCV care.